PENGARUH BUDAYA ORGANISASI DAN KEPUASAN KERJA TERHADAP KINERJA PEGAWAI PADA DINAS PERKEBUNAN, KEHUTANAN, DAN PERTAMBANGAN KABUPATEN KUBU RAYA - B31111043, RISKI JULIANDI (Jurnal Manajemen Update, 2017)
Dinas Perkebunan, Kehutanan, dan Pertambangan Kabupaten Kubu Raya. Tasks, functions and working procedures of the Department of Farming, Forestry and Mining Kubu Raya, in the implementation of the exercise of authority in the Local Government Sector Farming, Forestry and Mines as well as the duty of assistance provided by the Government. This study aims to analyze how much influence organizational culture and job satisfaction on the performance of the Dinas Perkebunan, Kehutanan, dan Pertambangan Kabupaten Kubu Raya. The population in this study were all employees in the Dinas Perkebunan, Kehutanan, dan Pertambangan Kabupaten Kubu Raya. The sample in this research is 57 respondents using simple random sampling technique sampling. Data analysis model used is the Multiple Linear Regression Analysis. Based on testing using t test concluded that the variables studied Organizational Culture proven to significantly affect the partial variable Employee Performance and Job Satisfaction studied variables found to significantly affect the partial variable Employee Performance Dinas Perkebunan, Kehutanan, dan Pertambangan Kabupaten Kubu Raya. Keywords : organizational culture, job satisfaction, and performance employee